Optimisation of mixed assets portfolio using copula differential evolution: A behavioural approach - Kofi A. Ababio; Jules Clement Mba; Ur Koumba (Cogent Economics & Finance, 2020)
Cumulative Prospect Theory (CPT) is rooted in behavioural psychology and has demonstrated to possess sufficient explanatory power for use in actual deci sion-making problems. In this study, two distinct asset classes (i.e. assets with extremely lower or higher CPT values) are classified and pre-selected for optimisa tion purposes using the differential evolution algorithm. Data on two asset classes namely cryptocurrencies and traditional indices were used in the study. The data were sourced from the Bloomberg database and spans the period August 2016 to March 2018. Probability weighting function with 1- and 2- parameters are used to obtain the CPT values of cryptocurrencies, indices, and mixed assets (i.e. crypto currencies and indices). We observe that portfolios consisting of assets of any kind with extremely lower CPT values generally outperform those with higher CPT values. Moreover, portfolios made up of mixed assets generate benefits in terms of improvement of the returns, but it tends also to increase volatility significantly.
Keywords: C02; G11; G17; 330; Cryptocurrencies indices; cumulative prospect theory; differential evolution copula; CVaR; portfolio optimisation